Reduction of malaria case incidence following the introduction of clothianidin-based indoor residual spraying in previously unsprayed districts: an observational analysis using health facility register data from Côte d’Ivoire, 2018–2022 - Patricia Yepassis-Zembrou; Sarah Burnett; Emily R Hilton; Allison Belemvire; Ndombour Gning-Cisse; Auguste Assi; Mathieu Eyakou; John Koffi; Barthelemy Gnakou; Bernard Kouassi; Cecilia Flatley; Joseph Chabi; et al. (BMJ Global Health)
Background Indoor residual spraying (IRS) using neonicotinoid-based insecticides (clothianidin and combined clothianidin with deltamethrin) was deployed in two previously unsprayed districts of Côte d’Ivoire in 2020 and 2021 to complement standard pyrethroid insecticide-treated nets. This retrospective observational study uses health facility register data to assess the impact of IRS on clinically reported malaria case incidence.Methods Health facility data were abstracted from consultation registers for the period September 2018 to April 2022 in two IRS districts and two control districts that did not receive IRS. Malaria cases reported by community health workers (CHWs) were obtained from district reports and District Health Information Systems 2. Facilities missing complete data were excluded. Controlled interrupted time series models were used to estimate the effect of IRS on monthly all-ages population-adjusted confirmed malaria cases and cases averted by IRS. Models controlled for transmission season, precipitation, vegetation, temperature, proportion of cases reported by CHWs, proportion of tested out of suspected cases and non-malaria outpatient visits.Results An estimated 10 988 (95% CI 5694 to 18 188) malaria cases were averted in IRS districts the year following the 2020 IRS campaign, representing a 15.9% reduction compared with if IRS had not been deployed. Case incidence in IRS districts dropped by 27.7% (incidence rate ratio (IRR) 0.723, 95% CI 0.592 to 0.885) the month after the campaign. In the 8 months after the 2021 campaign, 14 170 (95% CI 13 133 to 15 025) estimated cases were averted, a 24.7% reduction, and incidence in IRS districts dropped by 37.9% (IRR 0.621, 95% CI 0.462 to 0.835) immediately after IRS. Case incidence in control districts did not change following IRS either year (p>0.05) and the difference in incidence level change between IRS and control districts was significant both years (p<0.05).Conclusion Deployment of clothianidin-based IRS was associated with a reduction in malaria case rates in two districts of Côte d’Ivoire following IRS deployment in 2020 and 2021.